The Effect of Working Capital, Sales, and Cash Ratio on Profitability - Patamuan, Evodius; Karpriana, Angga P.; Yunita, Khristina (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze the effect of working capital, sales, and cash ratio on profitability at PT Indofood CBP Sukses Makmur during 2016-2020, using secondary data from the company's financial statements and multiple linear regression methods with Eviews. In 2017, the company's net profit decreased due to costs associated with launching new products to compete in the market. Nevertheless, product demand continued to grow among local and international customers, leading to an increase in working capital for marketing efforts. This study uses quantitative data from the financial statements of PT Indofood Sukses Makmur, analyzed using multiple linear regression to test the effect of working capital, sales, and cash ratio on profitability. The results of the study indicate that working capital does not have a significant impact on profitability due to ineffective turnover, in line with previous studies by Meidiyustiani (2016) and others. Sales have a negative impact on profitability, with high sales not covering the increase in operating costs. The cash ratio has a positive impact on profitability, although the impact is not significant, indicating that cash management is important but not the main driver of profit. Overall, this study shows that efficient use of working capital and cost management are key factors in increasing profitability.